2000
DOI: 10.1159/000024321
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous CD30+ Cells in Children with Atopic Dermatitis

Abstract: Background: CD30 expression can be considered a marker of Th2 cells. We investigated the presence of CD30+ cells in the lesional skin of children with atopic dermatitis (AD). We also analyzed the possible relationship between CD30+ cells and serum soluble CD 30 (sCD30) levels, and IgE, soluble interleukin-2 (IL-2) receptor (sIL-2R) or soluble CD23 (sCD23) levels in the blood, and clinical score. Methods: Ten eczematous children (4 males, 6 females; median age: 4 years and 5 months; range: 11 months to 14 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
9
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 26 publications
4
9
1
Order By: Relevance
“…Furthermore, a similar phenomenon has also been observed with paediatric patients [39–42], although one study reported a failure to associate sCD30 levels in cord blood with atopic disease at the age of 3 years [34]. However, some of these latter studies describe a lack of correlation between sCD30 levels and total serum IgE in children [34, 40, 41]. It is noteworthy that, in contrast to the previous reports with paediatric patients [39–41], we could not observe elevated sCD30 levels at 7 years of age in our children with atopic disease in general or AEDS in particular.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Furthermore, a similar phenomenon has also been observed with paediatric patients [39–42], although one study reported a failure to associate sCD30 levels in cord blood with atopic disease at the age of 3 years [34]. However, some of these latter studies describe a lack of correlation between sCD30 levels and total serum IgE in children [34, 40, 41]. It is noteworthy that, in contrast to the previous reports with paediatric patients [39–41], we could not observe elevated sCD30 levels at 7 years of age in our children with atopic disease in general or AEDS in particular.…”
Section: Discussionsupporting
confidence: 80%
“…However, there are certain other differences between these various studies that might explain the different results obtained. In the first place, circulating levels of sCD30 in children and young subjects have been shown to vary with age [37] and, in previous investigations [39–41], the age of the children included in the study groups varied, whereas we determined plasma sCD30 at three specific ages, i.e., at birth and at 2 and 7 years of age. Secondly, the criteria employed for the inclusion of subjects as well as for the evaluation of atopic disease might not have been identical in the different studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CD30 is expressed in a limited but increasingly reported number of inflammatory dermatoses including atopic dermatitis and arthropod bite reactions . Serum soluble CD30 has been shown to be increased in allergy and asthma in children , as well as in autoimmune disorders such as lupus and rheumatoid arthritis .…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…16,17 It has also been considered a diagnostic feature and a hallmark of cutaneous CD30 lymphoid proliferation (lymphomatoid papulosis/cutaneous CD30 + lymphoma). However, CD30 expression in large lymphoid cells can also be present in the inflammatory infiltrates of benign cutaneous disorders 18 such as atopic dermatitis, 19 drug reactions, 20 scabies, 21 and molluscum contagiosum infection. 22 CD30 expression on T cells has been proposed as a marker for type 2 helper T cells 23 induced by the T H 2 immune response.…”
Section: Discussionmentioning
confidence: 99%